2020
DOI: 10.1364/josab.398314
|View full text |Cite
|
Sign up to set email alerts
|

Counter-intuitive strength of electric field induced second harmonic (EFISH) signals at the rear side of thin silicon membranes

Abstract: Electric field induced second harmonic (EFISH) generation typically increases with laser intensity. Therefore, EFISH signals generated at the rear S i / S i O 2 interface by a laser beam transmitted through a thin silicon membrane should be much weaker than the signals generated in reflection at the front surface. The counter-intuitive finding that the signal generated at the rear surface is stronger than the front surface s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…(2) zyx    . (18) Here the 9 columns correspond to components xx, yy, zz, yz, zy, zx, xz, xy, yx, respectively. Therefore, the effective susceptibility tensor contains the component χ which is also the only second-order component different from zero for zincblende symmetry together with the following three independent components induced by the static field…”
Section: Efishmentioning
confidence: 99%
See 1 more Smart Citation
“…(2) zyx    . (18) Here the 9 columns correspond to components xx, yy, zz, yz, zy, zx, xz, xy, yx, respectively. Therefore, the effective susceptibility tensor contains the component χ which is also the only second-order component different from zero for zincblende symmetry together with the following three independent components induced by the static field…”
Section: Efishmentioning
confidence: 99%
“…Recently, it was also reported that ultrafast recombination together with carrier diffusion can be monitored by EFISH generated by space charge accumulation in the material. [4,17,18].…”
Section: Introductionmentioning
confidence: 99%